Interrelationships among diverse forms of social participation and their associations with basic psychological needs among older adults in Switzerland - Gashi, Shkumbin; Kaspar, Heidi; Holtforth, Martin grosse (Frontiers in Psychology, 2025)
Our aim was to identify which forms of social participation among older adults are associated with one another and how they relate to the satisfaction of basic psychological needs. Accordingly, we offer insights into the multiple roles older adults take on within their communities and how these roles relate to their wellbeing. We recruited participants for the study using a non-random, multi-pronged recruitment strategy through various channels. A sample of Swiss-based older adults (N = 286) completed an online survey containing demographic questions, measures of formal and informal social participation, and the Balanced Measure of Psychological Needs Scale by Sheldon and Hilpert (2012), validated in German by Neubauer and Voss (2016). Our results showed that older adults are active in diverse forms of social participation, highlighting a complex interconnectedness between multiple roles that they assume within their communities. However, the associations between different forms of social participation and the satisfaction of basic psychological needs were nuanced and selective. Through correlational and cluster analyses, we found that informal social participation was associated with balanced psychological needs satisfaction. Furthermore, both excessive and low engagement in certain forms of formal participation were linked to an imbalance in the satisfaction of basic psychological needs. Therefore, our findings inform practice by showing that to better support basic psychological needs satisfaction, informal participation should be prioritized, while formal participation should be personalized and monitored on how it is perceived by older adults, either as overly demanding or insufficiently challenging.